Chronic Stress Reduces Nectin-1 mRNA Levels and Disrupts Dendritic Spine Plasticity in the Adult Mouse Perirhinal Cortex - Gong, Qian; Su, Yun-Ai; Wu, Chen; Si, Tian-Mei; Deussing, Jan M.; Schmidt, Mathias V.; Wang, Xiao-Dong (Frontiers in Cellular Neuroscience, 2018)
In adulthood, chronic exposure to stressful experiences disrupts synaptic plasticity and cognitive function. Previous studies have shown that perirhinal cortex-dependent object recognition memory is impaired by chronic stress. However, the stress effects on molecular expression and structural plasticity in the perirhinal cortex remain unclear. In this study, we applied the chronic social defeat stress paradigm and measured the mRNA levels of nectin-1, nectin-3 and neurexin-1, three synaptic cell adhesion molecules implicated in the adverse stress effects, in the perirhinal cortex of wild-type and conditional forebrain corticotropin-releasing hormone receptor 1 knockout (CRHR1-CKO) mice. Chronic stress reduced perirhinal nectin-1 mRNA levels in wild-type but not CRHR1-CKO mice. In conditional forebrain corticotropin-releasing hormone overexpression (CRH-COE) mice, perirhinal nectin-1 mRNA levels were also reduced, indicating that chronic stress modulates nectin-1 expression through the CRH-CRHR1 system. Moreover, chronic stress altered dendritic spine morphology in the main apical dendrites and reduced spine density in the oblique apical dendrites of perirhinal layer V pyramidal neurons. Our data suggest that chronic stress disrupts cell adhesion and dendritic spine plasticity in perirhinal neurons, which may contribute to stress-induced impairments of perirhinal cortex-dependent memory.